Folklore Rules : A Fun, Quick, and Useful Introduction to the Field of Academic Folklore Studies - McNeill, Lynne S. (Book collections on Project MUSE., 2013)
"Folklore Rules is a brief introduction to the foundational concepts in folklore studies for beginning students. Designed to give essential background on the current study of folklore and some of the basic concepts and questions used when analyzing folklore, this short, coherent, and approachable handbook is divided into five chapters: What Is Folklore?; What Do Folklorists Do?; Things to Know about Folklore; Things to Know about Folk Groups; and, finally, What Do I Do Now? Through these chapters students are guided toward a working understanding of the field, learn basic terms and techniques, and learn to perceive the knowledge base and discourse frame for materials used in folklore courses. Folklore Rules will appeal to instructors and students for a variety of courses including introductory folklore and comparative studies as well as literature, anthropology, and composition classes that include a folklore component"--